Stimuli-responsive membrane activity of cyclic-peptide–polymer conjugates. Issue 21 (3rd May 2019) - Hartlieb, Matthias; Catrouillet, Sylvain; Kuroki, Agnès; Sanchez-Cano, Carlos; Peltier, Raoul; Perrier, Sébastien
Abstract : Cyclic peptide nanotubes were coupled to poly(oxazoline)s using a cleavable connection. Upon stimuli responsive detachment of the polymer an on-demand membrane activity could be achieved. Abstract : Cyclic peptide nanotubes (CPNT) consisting of an even number of amino acids with an alternating chirality are highly interesting materials in a biomedical context due to their ability to insert themselves into cellular membranes. However, unwanted unspecific interactions between CPNT and non-targeted cell membranes are a major drawback. To solve this issue we have synthetized a series of CPNT–polymer conjugates with a cleavable covalent connection between macromolecule and peptide. As a result, the polymers form a stabilizing and shielding shell around the nanotube that can be cleaved on demand to generate membrane active CPNT from non-active conjugates. This approach enables us to control the stacking and lateral aggregation of these materials, thus leading to stimuli responsive membrane activity. Moreover, upon activation, the systems can be adjusted to form nanotubes with an increased length instead of aggregates. We were able to study the dynamics of these systems in detail and prove the concept of stimuli responsive membrane interaction using CPNT–polymer conjugates to permeabilize liposomes as well as mammalian cell membranes.